Supply Chain Pattern in Digital for Government Pension Fund Management in Thailand - Artaphon Chansamut (ExcelingTech, 2022)
The paper was conducted to develop and evaluate supply chain pattern in digital for government pension fund management in Thailand. samples group in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on digital, Data were analysed by arithmetic mean and standard deviation. The paper findings pattern seven elements namely main components, Suppliers ,Manager , distributors, customers, consumers, satisfaction, feedback . The assessment supply chain pattern in digital for government pension management in Thailand using Black-Box technique and The results from experts agreement supply chain pattern in digital for government pension fund management in Thailand was a high level and can be applie in support the tasks.